2021
DOI: 10.1002/hep4.1810
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Safety of Repeated Acetaminophen Use in Patients With Compensated Cirrhosis

Abstract: Current guidelines recommend restricting acetaminophen (APAP) use in patients with cirrhosis, but evidence to support that recommendation is lacking. Prior studies focused on pharmacokinetics (PK) of APAP in cirrhosis but did not rigorously examine clinical outcomes, sensitive biomarkers of liver damage, or serum APAP-protein adducts, which are a specific marker of toxic bioactivation. Hence, the goal of this pilot study was to test the effects of regularly scheduled APAP dosing in a well-defined compensated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Although a common misconception, the short-term use of a low dose (2–3 g/day) of acetaminophen is safe in patients with ACLD [ 92 , 94 , 95 , 96 ]. In contrast, NSAIDs should be avoided in all ACLD patients, as they can precipitate AKI and gastrointestinal bleeding due to prostaglandin inhibition and increased bioavailability [ 94 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a common misconception, the short-term use of a low dose (2–3 g/day) of acetaminophen is safe in patients with ACLD [ 92 , 94 , 95 , 96 ]. In contrast, NSAIDs should be avoided in all ACLD patients, as they can precipitate AKI and gastrointestinal bleeding due to prostaglandin inhibition and increased bioavailability [ 94 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hypoglycemia can occur in patients with decompensated cirrhosis due to depletion in hepatic glycogen stores, impaired gluconeogenesis due to hepatocyte loss, and hyperinsulinemia. Continuous infusion of 10-20% dextrose can mitigate hypoglycemia, alt- Although a common misconception, the short-term use of a low dose (2-3 g/day) of acetaminophen is safe in patients with ACLD [92,[94][95][96]. In contrast, NSAIDs should be avoided in all ACLD patients, as they can precipitate AKI and gastrointestinal bleeding due to prostaglandin inhibition and increased bioavailability [94,97].…”
Section: Nutritionmentioning
confidence: 99%
“…However, a study showed that short-term administration of low-dose paracetamol is likely to be safe in patients with compensated cirrhosis. 140 In liver disease, the changes in individual enzymes that metabolize drugs in each patient are variable and do not closely correlate with clinical impairment as reflected by the Child-Pugh score. However, this is hardly surprising as this score is based exclusively on clinical attributes, and mostly derived from patients with decompensated cirrhosis.…”
Section: Efflux Transportmentioning
confidence: 99%
“…This effect is initiated by conversion of the drug, mostly via CYP2E1 and CYP1A2, to N‐acetyl‐p‐benzoquinone imine, an intermediate that in high quantity depletes the cells of glutathione. However, a study showed that short‐term administration of low‐dose paracetamol is likely to be safe in patients with compensated cirrhosis 140 …”
Section: Liver Disease and Its Effects On Drug Pkmentioning
confidence: 99%
“…APAP-protein adducts, measured as protein-derived APAP-cysteine (APAP-CYS) after the removal of free cysteine and proteolysis of the specimen, overcome some major shortcomings of serum APAP, APAP × AT, psi, and similar endpoints that are based on, or incorporate, serum APAP levels. Like APAP, adducts can become detectable in circulation as early as 1 h after a therapeutic dose, with a peak between 3 and 12 h after therapeutic or sub-hepatotoxic doses [81,82] and between 24 and 72 h after overdose [65] (similar to ALT), but they are more stable than APAP and decline slowly, with a half-life of 1-2 days [82-85] (Figure 3). Thus, serum adducts provide a longer diagnostic window than APAP alone.…”
Section: Diagnostic Utility Of Apap-protein Adducts As a Biomarkermentioning
confidence: 99%